"SIXTY-EIGHT WORKER IN THE SOUTH CONE"? CRISIS, STRIKES AND RADICALIZATION IN ARGENTINA AND CHILE, 1964 - 1970. - Thielemann Hernandez, Luis (Revista de Historia Social y de las Mentalidades, 2019)
Based on the available literature, the paper develops the question about the 1968 global workers' revolt, in Chile and Argentina. First, the stagnation and crisis of the "desarrollista" economic model is reviewed, as part of a global capitalist crisis that announced the revolts of "sixty-eight". Then, the striking rise and its common determinants on both sides of the Andes are analyzed, showing the regional coincidences. Finally, the radicalization of the regional workers in the period is analyzed, with a specific focus on the classist and autonomous attitudes of the workers' movement. It is proposed that it is possible to identify a "sixty-eight in the Southern Cone," assuming that the historical analysis of the general labor revolt process of the long global sixties cannot be limited to only one month, one year and one country.
Keywords: Global Sixty-eight; Global Sixties; Southern cone; Workers Movement